2014
DOI: 10.1213/ane.0000000000000392
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Signal Processing Used in the Implementation of the Pulse Oximetry Photoplethysmographic Fluid Responsiveness Parameter

Abstract: ΔPOP is a physiological parameter derived from the respiration-induced change in the pulse oximetry plethysmographic (POP) waveform or "pleth." It has been proposed as a proxy for pulse pressure variation used in the determination of the response to intravascular volume expansion in hypovolemic patients. Many studies have now reported on the parameter, and many research groups have constructed algorithms for its computation from the first principles where the implementation details have been described. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Obviously, the low and high frequency components of both the PPG and NIRS waveforms contain contributions from both arterial and venous blood, the relative amounts of which are not known. Of note, since the NIRS waveforms show the same respiratory variations as the arterial pressure [5] or PPG waveforms [6, 7], they might be used to non-invasively determine fluid responsiveness as well, particularly when peripheral perfusion is compromised.…”
Section: Near Infrared Spectroscopymentioning
confidence: 99%
“…Obviously, the low and high frequency components of both the PPG and NIRS waveforms contain contributions from both arterial and venous blood, the relative amounts of which are not known. Of note, since the NIRS waveforms show the same respiratory variations as the arterial pressure [5] or PPG waveforms [6, 7], they might be used to non-invasively determine fluid responsiveness as well, particularly when peripheral perfusion is compromised.…”
Section: Near Infrared Spectroscopymentioning
confidence: 99%
“…With vasodilatation, the plethysmogram amplitude is increased. 39 Addison 40 wrote a critical assessment of the use of the pulse oximetry plethysmogram waveform to assess fluid responsiveness. He provides a detailed overview of the signal processing methods used in individual studies, such as the details of exclusion criteria, manual filtering and preprocessing, gain change issues, acquisition details, selection of registration periods, averaging methods, and physiological influences on the plethysmogram.…”
Section: Fluid Responsivenessmentioning
confidence: 99%
“…39 Without the option to turn off this automatic resizing function, it is impossible to analyze the amplitude changes of the plethysmogram. Addison 40 suggests that more rigorous signal processing is required for a robust, fully automated ⌬POP algorithm for use in the clinical environment.…”
Section: Fluid Responsivenessmentioning
confidence: 99%
“…Through sophisticated signal processing it has been shown that these perturbations may be used to determine frequency of respiration (respiratory rate) using commercially available hardware [ 1 ]. DPOP (ΔPOP or Delta-POP) is a noninvasive parameter which measures the strength of respiratory modulations present in the pleth waveform [ 2 ]. It is defined as [ 3 ] where AMP max⁡ and AMP min⁡ are the maximum and minimum amplitudes of the cardiac pulse waveform in the pleth during a respiratory cycle.…”
Section: Introductionmentioning
confidence: 99%
“…As such it represents a noninvasive alternative for pulse pressure variation [ 4 ], a parameter derived from a blood pressure signal and widely used in practice for the prediction of the response to volume expansion in hypovolemic patients. PPV has the same mathematical formulation as DPOP [ 5 ] and many studies have shown favourable correlation between the two parameters [ 2 , 6 12 ]. The role of PPV as a surrogate parameter for stroke volume variation (SVV) and its use in determining where on the Frank-Starling curve the patient is operating is not described here; rather the reader is referred to [ 2 ] by the author which contains an in-depth treatment of the subject.…”
Section: Introductionmentioning
confidence: 99%